MODEL, MOTIVASI DAN KENDALA MASYARAKAT DALAM MELAKUKAN PERTANIAN KOTA (URBAN FARMING) DI KOTA SURABAYA - Parsudi, Setyo (Berkala Ilmiah AGRIDEVINA, 2019)
Urban farming can be a government effort to strengthen the country's food security, improve the economy of the people, improve the ecology of the city, maintain the social and cultural values ​​of Indonesia. In Surabaya there are still many people who aren’t maximal in applying the agriculture city, agriculture is still minimal so that the urban farming model that is implemented is still simple not in accordance with the situation without regard to its impact based on the background of this research. The purpose of this study is 1). Identify the application of urban farming models in the city of Surabaya 2). Knowing the motivation of the community to do urban agriculture and 3). Knowing the obstacles experienced by the community in implementing urban agriculture in the city of Surabaya. The results of the study found that the urban farming model that is mostly carried out by the people of Surabaya in sequence is hydroponics, followed by verticulture, fisheries and finally the rooftop garden. The motivation of the Surabaya community in conducting urban agriculture in sequence is mostly to increase income, utilize empty land, channel farming hobbies, and utilize green open space (RTH). Constraints or problems faced by the community in conducting urban agriculture are mostly sequentially attacked by plant pests, lack of capital to develop, barriers due to extreme weather and lack of experience and knowledge in urban agriculture. DOI : https://doi.org/10.33005/adv.v8i1.1612